Blood Pressure Increase during Oxygen Supplementation in Chronic Kidney Disease Patients Is Mediated by Vasoconstriction Independent of Baroreflex Function - van der Bel, René; Çalişkan, Müşerref; van Hulst, Robert A.; van Lieshout, Johannes J.; Stroes, Erik S. G.; Krediet, C. T. Paul (Frontiers in Physiology, 2017)
Renal hypoxia is thought to be an important pathophysiological factor in the progression of chronic kidney disease (CKD) and the associated hypertension. In a previous study among CKD patients, supplementation with 100% oxygen reduced sympathetic nerve activity (SNA) and lowered blood pressure (BP). We aimed to assess the underlying haemodynamic modulation and hypothesized a decreased systemic vascular resistance (SVR). To that end, 19 CKD patients were studied during 15-minute intervals of increasing partial oxygen pressure (ppO2) from room air (0.21 ATA) to 1.0 ATA and further up to 2.4 ATA, while continuously measuring finger arterial blood pressure (Finapres). Off-line, we derived indexes of SVR, cardiac output (CO) and baroreflex sensitivity from the continuous BP recordings (Modelflow). During oxygen supplementation, systolic and diastolic BP both increased dose-dependently from 128±24 and 72±19 mmHg respectively at baseline to 141±23 (p<0.001) and 80±21 mmHg (p<0.001) at 1.0ATA oxygen. Comparing baseline and 1.0 ATA oxygen, SVR increased from 1440±546 to 1745±710dyn·s/cm5 (p=0.009), heart rate decreased from 60±8 to 58±6 bpm (p<0.001) and CO from 5.0±1.3 to 4.6±1.1 L/min (p=0.02). Baroreflex sensitivity remained unchanged (13±13 to 15±12 ms/mmHg). These blood pressure effects were absent in a negative control group of eight young healthy subjects. We conclude that oxygen supplementation in CKD patients causes a non-baroreflex mediated increased in SVR and blood pressure.